Classroom Management Strategies for Creating a Conducive Learning Environment in Grade 3 at SD Muhammadiyah 4 Kandangsapi - Adelia Dwi Yulianti; Sukartono Sukartono; Minsih Minsih (Journal of Educational Sciences, 2026)
This study aims to describe classroom management strategies in creating a conducive learning environment in the third-grade classroom at SD Muhammadiyah 4 KandangSapi, as well as to identify supporting factors, obstacles, and solutions implemented by teachers. The research uses a qualitative approach with a case study design to gain an in-depth understanding of classroom practices in a real context. The subjects include the third-grade teacher as the main informant, students as supporting informants, and the principal as an additional informant. Data were collected through passive participatory observation, semi-structured interviews, and documentation, and analyzed using the Miles and Huberman interactive model, including data reduction, data presentation, and conclusion drawing, with triangulation to ensure validity. The findings show that classroom management is carried out systematically through initial conditioning, organizing the learning environment, enforcing classroom rules, and managing student behavior. Supporting factors include collaboration, adequate facilities, and school support. Meanwhile, obstacles involve differences in student characteristics, limited classroom space, and less conducive classroom conditions. To address these challenges, teachers apply adaptive solutions such as personalized approaches, collaboration with parents, and varied teaching methods to increase student engagement. This study highlights the importance of flexible and context-based classroom management strategies tailored to elementary students’ needs.